Managing Creative Skills to Increase the Economic Efficiency of Industrial Organizations - Jasim, Haider Mohammed; Bisheen, Ali Saud; Almrshed, Sattar Kadim Hachim (South Asian Journal of Social Sciences and Humanities, 2023)
Economic variations have generated the need for the request of innovative management and management methods and approaches that would advance employees’ different thinking "problem solving ability" and mobilize their original potential. Creativity becomes one of the main managerial abilities. Therefore, the article deals with the concept of creative skills management systems of industrial enterprises. The main goal and tasks in the management of creative skills, and the ways of management decisions .also, the model of an industrial enterprise’s creative skills management subsystem is presented. In order to evaluate the administrative system of creative skills in the Iraqi Cement state Company, management, Management Functional Assessment Model (MFAM) was used, and the sample was 173 employees. We also consider the main indicators for evaluating the effectiveness of the creative skills management system in order to ensure efficiency growth in the conditions of innovative economic development. After conducting the tests, it became clear the importance of creative skills management in order to increase the economic efficiency of companies and its role in developing the performance of employees. Also, companies gain a continuous and increasing competitive advantage by owning innovative employees. In addition, the study recommends paying attention to creative skills and developing them in order to increase the performance of employees and raise the economic efficiency of companies and possess a competitive advantage.